Reviewing Performance or Changing Routines? An Analysis of the Experience of Participants in Performance Management Review Meetings - Pavlov, Andrey (Cranfield University, 2010)
The problem examined in this thesis falls under the broad question of the nature of effect of performance measurement and management (PMM) on organizational performance. Responding to the unsuccessful attempts of the current literature to produce conclusive evidence of the effect of PMM on performance and building on the recent studies documenting the effect of PMM on organizational processes, the work reported in this thesis employs the organizational routines perspective as an analytical lens for examining the way in which a particular PMM practice – a performance management review meeting – affects organizational processes that generate performance. More specifically, the study uses Feldman and Pentland’s (2003) model of routines in order to explore the ways in which organizational actors experience the ostensive aspect of organizational routines in the context of a performance management review meeting. Based on two case studies conducted in the UK in 2009, the thesis develops a model suggesting that performance management review meetings influence the dynamics of organizational routines by affecting a number of specific processes that constitute the engagement of the participants at the meeting with the ostensive aspect of the routine. The results highlight the critical role of attention in these processes and suggest a number of ways in which the attention of the participants may be influenced. As such, the study explicates the micro dynamics of the link between a PMM intervention in the form of the performance management review meeting and the organizational processes that generate performance, thus making a step towards increasing the understanding of the direct impact of PMM on performance.